Use of Recycled Automobile Tires to Design Landfill Components. Issue 3 (1st January 1995) - Shettima, M.; Narejo, D.B.
Abstract : There are several possible uses of recycled automobile tires in the design of landfill liner and cover system components. This technical note examines the use of recycled tires for geomembrane protection, drainage, friction sheets, select fill and daily cover. The performance data obtained thus far, using standard test methods, are presented. Where possible, the performance data for recycled tire products was compared with performance data for traditional engineering materials. Recommendations for evaluating the durability and compatibility of recycled tire products are also presented.